2003
DOI: 10.1086/376917
|View full text |Cite
|
Sign up to set email alerts
|

Are Hummingbirds Facultatively Ammonotelic? Nitrogen Excretion and Requirements as a Function of Body Size

Abstract: Most birds are uricotelic. An exception to this rule may be nectar-feeding birds, which excrete significant amounts of ammonia under certain conditions. Although ammonia is toxic, because it is highly water soluble its excretion may be facilitated in animals that ingest and excrete large amounts of water. Bird-pollinated plants secrete carbohydrate- and water-rich floral nectars that contain exceedingly little protein. Thus, nectar-feeding birds are faced with the dual challenge of meeting nitrogen requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 57 publications
0
20
1
Order By: Relevance
“…Protein intake had the opposite effect on these two metabolites. Ammonotely in the yellow-vented bulbul McWhorter et al, 2003). The nitrogen requirements of both bulbuls and grackles were extremely low.…”
Section: Low Nitrogen Requirements In Yellow-vented Bulbuls Andmentioning
confidence: 96%
See 1 more Smart Citation
“…Protein intake had the opposite effect on these two metabolites. Ammonotely in the yellow-vented bulbul McWhorter et al, 2003). The nitrogen requirements of both bulbuls and grackles were extremely low.…”
Section: Low Nitrogen Requirements In Yellow-vented Bulbuls Andmentioning
confidence: 96%
“…The hypothesis of Preest and Beuchat (1997) proposes that high energy demands and high water fluxes favor ammonotely. McWhorter et al (2003) challenged the generality of Preest and Beuchat's results (Preest and Beuchat, 1997). They fed black-chinned hummingbirds Archilochus alexandri, magnificent hummingbirds Eugenes flugens and blue-throated hummingbirds Lampornis clemenciae dilute, protein-poor diets, but found that neither of these species became ammonotelic.…”
mentioning
confidence: 98%
“…A similar pattern was found previously in G. soricina: bats on energy-poor diets (5 and 10% sucrose) had similar or higher N intakes but lower N balances than bats on energy-rich diets [20 and 30% sucrose (Herrera M. et al, 2006)]. A relationship between energy content of the diet and N balance was previously reported in A. jamaicensis: when offered diets with contrasting energy density (2.5-2.9 vs 3.1-3.5kJg -1 wetmass), bats had lower N balance on the diet with less energy density (Delorme and Thomas, 1999 (McWhorter et al, 2003;Tsahar et al, 2005)]. Most bats on the energy-poor diet had a daily N ingestion above MNR, but were in negative balance.…”
Section: N Balancementioning
confidence: 78%
“…The urea concentrations seen in these gulls would have had a serious detrimental effect on protein function throughout the body (Morgan et al ., 2003). Marine elasmobranchs are the only animals that are adapted to cope with plasma urea concentrations in the 300 to 600 mM range (Part et al ., 1998;Withers et al, 1994;Fines et al ., 2001), and they do so by accumulating methylamines and other low-molecularweight osmolytes that offset the effects of urea on proteins (Lee et al ., 1991;Withers et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Avian arginase can be upregulated in birds fed high-protein diets and is inhibited by adenosine triphosphate, so when energy is not limited urea is not produced (Ruiz-Feria et al ., 2001;Koutsos et al ., 2001). In low ambient temperatures, some nectarivorous birds may conserve energy by increasing urea excretion and lowering uric acid excretion; hummingbirds can even excrete up to 50% of waste nitrogen as ammonia provided that water intake is not limited (Preest & Beuchat, 1997;Roxburgh & Pinshow, 2002;McWhorter et al ., 2003). However, this has not been demonstrated in non-nectarivorous species (Sabat et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%